Filosofie op Potchefstroom die afgelope eeu (1917-2017), deel 4, Op die tweesprong? - Walt, Barend Johannes van der (Koers, 2019)
Philosophy at Potchefstroom the past century(1917-2017). Part 4: At the cross-roads? Three previous articles in this journal reviewed the history of philosophy at Potchefstroom from the beginning of the previous century up to about 2009. In this and the next contribution the writer, acting again as a fly on the wall, provides a peephole on the current situation at the end of 2017. As the subtitle suggests, it seems that Christian philosophy at Potchefstroom has arrived at the cross-roads. Different reasons, like the on-going secularisation of the North-West University have contributed to the situation. A cause for differences within the School of Philosophy may also be that lecturers from outside the tradition of a Reformational approach are critical about the traditional Christian philosophical approach of more than a century. Since his viewpoint is one clear example of such an alternative approach the academic training, publications and viewpoint of Prof Anné H. Verhoef will be investigated in detail in a last (fifth) contribution. The present article about the main contours of a Reformational approach in philosophy serves as a necessary background from which the philosophical theology of Verhoef will be analysed and evaluated in the conclusion of this series.